INvolvement of breast CAncer patients during oncological consultations: a multicentre randomised controlled trial—the INCA study protocol. Issue 5 (2nd May 2013) - Goss, Claudia; Ghilardi, Alberto; Deledda, Giuseppe; Buizza, Chiara; Bottacini, Alessandro; Del Piccolo, Lidia; Rimondini, Michela; Chiodera, Federica; Mazzi, Maria Angela; Ballarin, Mario; Bighelli, Irene; Strepparava, Maria Grazia; et al.
Abstract : Introduction: Studies on patient involvement show that physicians make few attempts to involve their patients who ask few questions if not facilitated. On the other hand, the patients who participate in the decision-making process show greater treatment adherence and have better health outcomes. Different methods to encourage the active participation during oncological consultation have been described; however, similar studies in Italy are lacking. The aims of the present study are to (1) assess the effects of a preconsultation intervention to increase the involvement of breast cancer patients during the consultation, and (2) explore the role of the attending companions in the information exchange during consultation. Methods and analysis: All female patients with breast cancer who attend the Oncology Out-patient Services for the first time will provide an informed consent to participate in the study. They are randomly assigned to the intervention or to the control group. The intervention consists of the presentation of a list of relevant illness-related questions, called a question prompt sheet. The primary outcome measure of the efficacy of the intervention is the number of questions asked by patients during the consultation. Secondary outcomes are the involvement of the patient by the oncologist; the patient's perceived achievement of her information needs; the patient's satisfaction and ability to cope; the quality of the doctor–patient relationship in terms of patient-centeredness; and the number of questions asked by the patient's companions and their involvement during the consultation. All outcome measures are supposed to significantly increase in the intervention group. Ethics and dissemination: The study was approved by the local Ethics Committee of the Hospital Trust of Verona. Study findings will be disseminated through peer-reviewed publications and conference presentations. Trial registration: ClinicalTrials.gov identifier: NCT01510964